Aplikasi Sistem Pakar Diagnosa Penyakit Pada Kucing Menggunakan Algoritma Certainty Factor Berbasis Web - Handayani, Dwipa; Mahbub, Asep Ramdhani; Noeman, Achmad; Febian, Guruh Putra; Lubis, Hendarman (Journal of Information System, Informatics and Computing, 2025)
This web-based expert system for diagnosing cat diseases is designed to provide fast and accurate diagnoses. Cat owners can input observed symptoms, which are then analyzed using the Certainty Factor algorithm to calculate the likelihood of possible diseases. Based on test data, the system achieves up to 90% accuracy for common diseases such as Feline Panleukopenia Virus and Feline Calicivirus. The algorithm handles uncertainty by generating values between 0 and 1, indicating the confidence level of each diagnosis. Built with PHP and MySQL, the system is accessible in real-time through a responsive web interface. This enhances the efficiency of disease diagnosis and reduces the reliance on veterinarians for initial assessments. Moreover, the system contributes to the advancement of expert system technology in animal health by integrating the proven effectiveness of the Certainty Factor algorithm.